Pengaruh Kualitas Audit dan Financial Distress terhadap Integritas Laporan Keuangan: Studi Empiris pada Perusahaan Sub Sektor Keuangan dan Perbankan yang terdaftar di Bursa Efek Indonesia 2019-2023 - Melinda Febriyanti; Johannes Kristian Siregar; Antonius Bimo Rentor Luntungan (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study aims to analyze the effect of audit quality and financial distress on the integrity of financial statements in financial and banking sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. The integrity of financial statements is a critical factor in maintaining stakeholders’ trust in the financial information presented by companies. A quantitative approach is used in this study, employing multiple linear regression analysis. Audit quality is measured using audit opinions (Unqualified and Non-Unqualified), while financial distress is assessed using the Z-score method. In this study, audit quality did not affect the integrity of financial reports, while financial distress did. Audit quality and financial did. Audit quality and financial distress jointly affected the integrity of financial reports.